2013
DOI: 10.1080/03075079.2011.626851
|View full text |Cite
|
Sign up to set email alerts
|

Technology-mediated supervision of undergraduate students' dissertations

Abstract: In Sweden, technology-mediated participation has increased in tertiary education, which has led to changing conditions for its delivery. However, one part has proven more resistant to change, technology-mediated or not: the supervision of students' undergraduate dissertation work. This article presents a study that analyses technological applications to mediate supervision of students' undergraduate dissertation work. It is shown that students in general find such mediated participation helpful for supervision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 28 publications
0
22
0
3
Order By: Relevance
“…Literature on student satisfaction in higher education has considered a range of aspects from various perspectives. Some studies have focused on the level of student satisfaction with one or more subjects [17][18][19][20][21][22][23][24], whilst others address satisfaction with university degrees or university institutions [25,26]. In many of these studies, satisfaction is associated with other variables such as utility, motivation or skills acquisition, albeit not jointly.…”
Section: Student Satisfactionmentioning
confidence: 99%
“…Literature on student satisfaction in higher education has considered a range of aspects from various perspectives. Some studies have focused on the level of student satisfaction with one or more subjects [17][18][19][20][21][22][23][24], whilst others address satisfaction with university degrees or university institutions [25,26]. In many of these studies, satisfaction is associated with other variables such as utility, motivation or skills acquisition, albeit not jointly.…”
Section: Student Satisfactionmentioning
confidence: 99%
“…The only example of a similar system Essop (2013) found was developed in Ireland for offcampus supervision (MacKeogh, 2008), although Jaldemarka and Lindberg (2013) have subsequently published research into technology-mediated supervision of dissertations in Sweden. They showed that the supervision of students' undergraduate dissertation work has proved resistant to change, whether technology-mediated or not, but that students in general find such mediated participation helpful for supervision and they suggested that mediation by technology is a productive way to enhance the supervision of students' undergraduate dissertations.…”
Section: Figure 4: Proposed Student Dashboardmentioning
confidence: 99%
“…Figure 15 highlights that staff and student resistance to change is the main inhibitor for innovation (this is also covered by Jones et al 2012;Jaldemark & Lindberg 2013;Newland & Byles 2014).…”
Section: The Value Of Staff Training Is Also Reflected In the Responsmentioning
confidence: 99%
“…While the reduction in public funds can make implementing innovations difficult because of a lack of resources, it might also stimulate higher education institutions to change by 'doing more with less', sometimes on a for-profit basis (Harloe & Perry 2004;Alexander 2006;Redecker et al 2009;Chester et al 2013;Istance & Kools 2013;Jaldemark & Lindberg 2013;Newland & Byles 2014). Indeed, Figure 18 shows that 27 out of 32 respondents to the survey indicated that the increasing need and pressure for efficiency and better use of resources (due to growing resource constraints) has been a key external driver of innovation in their institution.…”
Section: Government Funding To Higher Education Institutions and Fundmentioning
confidence: 99%
See 1 more Smart Citation